Transition Into HE: The Views and Experiences of Learners with Physical Needs - Packer, Rhiannon; Abbinett, Emily; Pierce, Adam; Smith, Paul (International Journal of Educational and Life Transitions, 2024)
This article draws on data gathered to explore experiences of students with a physical need in Higher Education (HE). Participants were recruited from several HE institutions using purposive sampling. Drawing upon Jindal-Snape’s (2023) Multiple and Multi-dimensional Transitions theory the article acknowledges the complexity and diversity of individual experiences while recognising the role of dispositions and environmental factors in supporting successful transition. This scoping exercise delved into the personal experiences of 7 individuals who were either current or recent students at several HE institutions. Initial findings are that despite an increase in the numbers of students entering HE with a known disability, environmental and infra-structural barriers remain for these students both prior to transition and during their time at university. Findings from in-depth interviews led to 3 principal recommendations for reflection and change by HE institutions: a need for a systematic and comprehensive review of provision across University departments to ensure a joined-up approach with regards to accessibility needs; further considerations of both environmental and curricular barriers that create social and academic exclusion; and the engagement of those with lived experience to inform policy and support change in what can be considered a dynamic environment. Regular individual HE reviews and ongoing amendments to support learners with physical needs are recommended.
Keywords: higher education (HE); disability; physical needs; accessibility; barriers to learning; inclusive education